Improving mental health among pediatric critical care survivors - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Elisa Nugraha Haryadi Salakay (Journal of Pediatric Critical Care)
Effective pediatric critical care is vital in improving survival rates, with many children recovering from a spectrum of conditions that were once considered fatal. Even though survival rates have improved, recent available estimates highlight the long-term physical, cognitive, and psychological consequences of critical illness, including difficulties in social reintegration. A wide range of risk factors have been identified that can cumulatively contribute to the mental health concerns identified among pediatric critical care survivors. As the development of mental health disorders among pediatric critical care survivors can impair the quality of life and add a financial burden, there is an indispensable need to identify the existing challenges and implement strategies to overcome them. In conclusion, the mental health consequences among pediatric critical care survivors can be devastating. The need of the hour is to adopt a comprehensive approach that extends beyond acute care, including strengthening mental health support, rehabilitation services, and awareness activities targeting caregivers and school staff.